Analysis of the level of integration of the supply chain of a food industry in the west of Santa Catarina - Zanella, Cleunice; Veroneze, Silvana; Leite, Maurício; Martini, Raphael; Barichello, Rodrigo (Revista de Administração da UFSM, 2023)
Objective: The study aims to analyze the level of integration of the supply chain of a food industry located in the western region of Santa Catarina. Methodology: this is a case study with a qualitative approach. For data collection, the AGA methodology (Assessment of Degree of Adherence) by Lambert and Cooper (2000), adapted by Simon (2005; 2014) was used. Findings: the results show that the focal company has an "A" level of adherence, indicating a high power of influence and performance in chain management, both for the incorporation of innovations aimed at sustainable practices and for monitoring more responsible organizational processes, processes and relationships throughout the supply chain. This elevated level of integration may be associated with the elevated level of vertical integration in the chain, coordinated by the focal company. Research limitations: the results obtained can only be applied to the focal company and cannot be generalized to all companies. In addition, other evaluation metrics and/or endogenous variables not considered in this study may influence the results achieved. Originality/value: the originality of the study converges with the lack of studies that address the application of methodologies for evaluating the degree of interaction in the supply chain in the food industry segment. Thus, it is expected that the results of the study can be used as an instrument for analysis and reflection on the level of integration of supply chains, as well as to identify potential barriers to the implementation of supply chain management practices.